2014
DOI: 10.5812/ircmj.19329
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Safety of Propofol Versus Midazolam/Meperidine Sedation for Colonoscopy: A Prospective, Randomized, Double-Blinded Study

Abstract: Background:Different levels of pharmacological sedation ranging from minimal to general anesthesia are often used to increase patient tolerance for a successful colonoscopy. However, sedation increases the risk of respiratory depression and cardiovascular complications during colonoscopy.Objectives:We aimed to compare the propofol and midazolam/meperidine sedation methods for colonoscopy procedures with respect to cardiopulmonary safety, procedure-related times, and patient satisfaction.Patients and Methods:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this study, patients’ hemodynamic variables were monitored intraoperatively, and regarding the cardiovascular effects of opioids, no significant difference was observed between the study groups. Gurbulak et al ( 32 ) also found no association between incidence rates of cardiopulmonary events and the use of propofol or midazolam/meperidine. Respiratory depression is a rare side effect of intrathecal opioids caused by suppression of the respiratory centers in the brainstem ( 33 ).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, patients’ hemodynamic variables were monitored intraoperatively, and regarding the cardiovascular effects of opioids, no significant difference was observed between the study groups. Gurbulak et al ( 32 ) also found no association between incidence rates of cardiopulmonary events and the use of propofol or midazolam/meperidine. Respiratory depression is a rare side effect of intrathecal opioids caused by suppression of the respiratory centers in the brainstem ( 33 ).…”
Section: Discussionmentioning
confidence: 96%
“…Compared to other Turkish cohorts, the number of events observed during the baseline is lower than in previous publications reporting on propofol sedation. Gurbulak et al compared the safety of propofol with midazolam/medperidine sedation for colonoscopic procedures, reporting an 8.1% incidence of oxygen desaturation events in the propofol arm [ 16 ]. In our evaluation, if only colonoscopy is considered, only 4.03% of procedures were associated with any oxygen desaturation event (mild and severe desaturations).…”
Section: Discussionmentioning
confidence: 99%
“…In our evaluation, if only colonoscopy is considered, only 4.03% of procedures were associated with any oxygen desaturation event (mild and severe desaturations). In the same study, bradycardias also were registered, but none were found in the propofol arm [ 16 ]. This matches our analysis, as only a single adverse event of bradycardia was observed for the 264 patients receiving gastroscopy only.…”
Section: Discussionmentioning
confidence: 99%